TouchTerrain: A simple web-tool for creating 3D-printable topographic models. (December 2017) - Hasiuk, Franciszek J.; Harding, Chris; Renner, Alex Raymond; Winer, Eliot
Abstract: An open-source web-application, TouchTerrain, was developed to simplify the production of 3D-printable terrain models. Direct Digital Manufacturing (DDM) using 3D Printers can change how geoscientists, students, and stakeholders interact with 3D data, with the potential to improve geoscience communication and environmental literacy. No other manufacturing technology can convert digital data into tangible objects quickly at relatively low cost; however, the expertise necessary to produce a 3D-printed terrain model can be a substantial burden: knowledge of geographical information systems, computer aided design (CAD) software, and 3D printers may all be required. Furthermore, printing models larger than the build volume of a 3D printer can pose further technical hurdles. The TouchTerrain web-application simplifies DDM for elevation data by generating digital 3D models customized for a specific 3D printer's capabilities. The only required user input is the selection of a region-of-interest using the provided web-application with a Google Maps-style interface. Publically available digital elevation data is processed via the Google Earth Engine API. To allow the manufacture of 3D terrain models larger than a 3D printer's build volume the selected area can be split into multiple tiles without third-party software. This application significantly reduces the time and effort required for a non-expert like an educator to obtain 3D terrain models for use in class. The web application is deployed at http://touchterrain.geol.iastate.edu, while source code and installation instructions for a server and a stand-alone version are available at Github: https://github.com/ChHarding/TouchTerrain_for_CAGEO . Highlights: Web-tool makes 3D printable digital models from public elevation data. Python code uses Google Earth Engine API to process elevation data. 3D models use 3D printer constraints making Direct Digital Manufacturing possible. 3D Printed models can be tiled to overcome size limitation of 3D printers.